Generalized Variational Oscillation Principles for Second-Order Differential Equations with Mixed-Nonlinearities - Jing Shao; Fanwei Meng; Xinqin Pang (Discrete Dynamics in Nature and Society)
Using generalized variational principle and Riccati technique, new oscillation criteria are established for forced second-order differential equation with mixed nonlinearities, which improve and generalize some recent papers in the literature.